A ação das palavras na Electra de Sófocles - Silva, Rafael Guimarães Tavares da (2023)
Traditional studies dedicated to Sophocles' tragedy Electra have emphasized a dichotomy between Electra's long dismal speeches, especially in the first half of the play, and the efficiency of Orestes' actions to carry out the outcome of the plot. Seeking support from contemporary commentators on this work, who have emphasized the performative dimension of certain speech acts there, I intend to revisit this discussion in order to elicit a new possibility of considering Electra's role in the play. The interpretation suggested here accounts for certain strangeness of this tragic text and advances a better understanding of some details of the scene in which Clytemnestra is murdered, as well as the seemingly amoral conclusion advanced by the way the work ends, without the matricide seeming to have any harmful consequences (as it happens in the versions that Aeschylus and Euripides propose of this same mythic event).